2021
DOI: 10.1051/0004-6361/202039951
|View full text |Cite
|
Sign up to set email alerts
|

Abundance–age relations with red clump stars in open clusters

Abstract: Context. Precise chemical abundances coupled with reliable ages are key ingredients to understanding the chemical history of our Galaxy. Open clusters (OCs) are useful for this purpose because they provide ages with good precision. Aims. The aim of this work is to investigate the relation between different chemical abundance ratios and age traced by red clump (RC) stars in OCs. Methods. We analyzed a large sample of 209 reliable members in 47 OCs with available high-resolution spectroscopy. We applied a differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 79 publications
8
36
0
Order By: Relevance
“…These relations can be explained with similar arguments as [Y/Mg], which is widely discussed in the literature (e.g. Nissen 2015;Delgado Mena et al 2019;Casamiquela et al 2021). The argument is the very different timescales for the production of an alpha-capture element such as Mg in comparison with a neutron-capture element such as Y.…”
Section: Chemical Clockssupporting
confidence: 60%
See 3 more Smart Citations
“…These relations can be explained with similar arguments as [Y/Mg], which is widely discussed in the literature (e.g. Nissen 2015;Delgado Mena et al 2019;Casamiquela et al 2021). The argument is the very different timescales for the production of an alpha-capture element such as Mg in comparison with a neutron-capture element such as Y.…”
Section: Chemical Clockssupporting
confidence: 60%
“…When combined, a tight relation of [Y/Mg] can be found for stars of the same metallicity but different ages. Jofré et al (2020) and Casamiquela et al (2021) found that the clocks showing largest age dependency involved neutron-Figure 5. Differential abundance as a function of elemental condensation temperature from the H20 systems and our sample of wide binaries that present a slope greater than 3 × 10 −5 dex/K.…”
Section: Chemical Clocksmentioning
confidence: 99%
See 2 more Smart Citations
“…Spina et al 2016;Delgado Mena et al 2019;Jofré et al 2020), the next steps were the following: i) to clarify the applicability of these relationships with luminosity class (dwarf or giant) (see, e.g. Tucci Maia et al 2016b;Slumstrup et al 2017;Casamiquela et al 2021), metallicity (see, e.g Feltzing et al 2017Delgado Mena et al 2019;Casali et al 2020), and population type (thin disc, thick disc, halo) (see, e.g. Titarenko et al 2019;Nissen et al 2020;Tautvaišienė et al 2021), or even in dwarf galaxies (Skúladóttir et al 2019); ii) to calibrate them with a sample of stars with reliable age determination, which are usually open star clusters (OCs), solar twins, or targets with asteroseismic observations.…”
Section: Introductionmentioning
confidence: 99%